Hydroxycitric acid reconstructs damaged articular cartilages by modifying the metabolic cascade in chondrogenic cells - Mizushina, Yoshiyuki; Sun, Liping; Nishio, Megumi; Nagata, Sanae; Kamakura, Takeshi; Fukuda, Masayuki; Tanaka, Kousuke; Toguchida, Junya; Jin, Yonghui (Osteoarthritis and cartilage open, 2025)
Osteoarthritis, a degenerative joint disease, requires innovative therapies due to the limited ability of cartilage to regenerate. Since mesenchymal stem cells (MSCs) provide a cell source for chondrogenic cells, we hypothesize that chemicals capable of enhancing the chondrogenic potential of MSCs with transforming growth factor-beta (TGFβ) in vitro may similarly promote chondrogenesis in articular cartilage in vivo. Chemical compounds that enhance the TGFβ signaling for chondrogenesis were investigated utilizing mesenchymal stem cells derived from human induced pluripotent stem cells. The mechanisms of action underlying the identified compound were explored in vitro, and its therapeutic effects were validated in vivo using a mouse model of exercise-induced osteoarthritis. Hydroxycitric acid (HCA) emerged as the lead compound. In vitro, HCA effectively enhanced chondrogenesis by inhibiting ATP citrate lyase, inducing citrate and alpha-ketoglutarate (α-KG), while reducing cytosolic acetyl coenzyme A (Ac-CoA). This induction of α-KG promoted collagen prolyl-4-hydroxylase activity, boosting hydroxyproline production and matrix formation. The reduction of Ac-CoA attenuated the inhibitory effect of β-catenin on mitochondrial activity by diminishing its acetylation. In vivo, orally administered HCA accumulated in joint tissues of mice and histological examination demonstrated newly synthesized cartilage tissues in damaged area. Analysis of joint tissue extracts revealed a downregulation of Ac-CoA and an upregulation of citrate and α-KG, accompanied by a systemic increase in an anabolic biomarker. HCA demonstrates promise as an osteoarthritis therapy by enhancing chondrogenic differentiation. Its ability to modulate crucial metabolic pathways and facilitate cartilage repair suggests potential for clinical translation, addressing a critical need in the treatment of osteoarthritis.